Serum progesterone and retinopathy in male patients with type 2 diabetes: A cross‐sectional study - Sun, Shengnan (J Diabetes Investig, 2020)
AIMS/INTRODUCTION: The aim of this study was to investigate the relationship between serum progesterone (P) and retinopathy in male patients with type 2 diabetes mellitus, and to investigate whether P is associated with its progression. MATERIALS AND METHODS: A total of 1,376 male participants with type 2 diabetes mellitus were recruited from Affiliated Hospital of Medical College Qingdao University (Qingdao, China). Through logistic regression analysis after adjusting the potential confounding variation, the odds ratio (OR) and the corresponding 95% confidence interval related to the quartiles of progesterone were obtained. RESULTS: According to the quartiles of P levels, the prevalence rate of diabetic retinopathy (DR) in the last quartile is obviously greater to other quartiles (52.5–34.9%, 31.9%, 37.5%, P < 0.001). Compared with those in the first quartile, the prevalence of DR for the last quartile had an OR of 1.85 in the non‐proliferative diabetic retinopathy group, while the OR was 8.35 in the proliferative diabetic retinopathy group (P < 0.001, unadjusted model). When adjusted for age, body mass index, duration of type 2 diabetes mellitus, glycated hemoglobin, blood pressure and other variables, the ORs for DR in the fourth quartile were 2.13 (95% confidence interval 1.49–3.06) in the non‐proliferative diabetic retinopathy group and 8.44 (95% confidence interval 2.69–26.43) in the proliferative diabetic retinopathy group (P < 0.001). The positive association between P and DR risk was independent in adjusted logistic regression. CONCLUSIONS: High levels of serum progesterone are significantly associated with DR in male hospitalized patients. This could mean that a higher P level in men is a potential clinical factor to identify DR, and the causality remains to be further explored.